RONC-09. META-ANALYSIS OF THE INCIDENCE AND PATTERNS OF SECOND NEOPLASMS AFTER PHOTON CRANIOSPINAL IRRADIATION IN CHILDREN WITH MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Bavle, Abhishek; Tewari, Sayani; Sisson, Amy; Chintagumpala, Murali; Anderson, Michael; Paulino, Arnold
Abstract: BACKGROUND: Second neoplasms (SNs) are a well-established long-term adverse effect of radiation therapy (RT), but there is limited data regarding their incidence and location relative to the radiation field, specific to medulloblastoma (MB) survivors after craniospinal irradiation (CSI). METHODS: A systematic literature review, per PRISMA, identified 6 studies reporting the incidence and locations of SNs, for 1114 patients with MB, after CSI, with median follow-up of at least 5 years. The study-specific cumulative incidence (CI) of second neoplasms (SNs), second benign neoplasms (SBNs) and second malignant neoplasms (SMNs) were standardized to a 10-year time-frame. Meta-analysis was performed using mixed and random effects models, with pooled data from selected studies, and an institutional cohort of 55 patients. RESULTS: The 10-year CI was 6.1% for all SNs (excluding skin cancer and leukemia), 3.1% for SBNs and 3.7% for SMNs. Sixty percent of SNs were malignant; high-grade glioma was the most common SMN (15/33; 45%) and meningioma was the most common SBN (17/24; 71%). Forty percent of SNs occurred outside the CNS, primarily outside the target, but in areas of exit RT dose. Seventy eight percent of extra-CNS tumors (18/23) were malignant, most commonly thyroid carcinoma (8/18; 44%) and bone and soft tissue sarcomas (6/18, 33%). CONCLUSIONS: Survivors of medulloblastoma are at risk of SNs both within and outside the CNS, in areas of exit RT dose. Studies are needed to determine whether the use of proton therapy, which has no exit RT dose, is associated with a lower incidence of SNs.